Simplifying
p^{2} + 21p + -49 = 21p
Reorder the terms:
-49 + 21p + p^{2} = 21p
Add '-21p' to each side of the equation.
-49 + 21p + -21p + p^{2} = 21p + -21p
Combine like terms: 21p + -21p = 0
-49 + 0 + p^{2} = 21p + -21p
-49 + p^{2} = 21p + -21p
Combine like terms: 21p + -21p = 0
-49 + p^{2} = 0
Solving
-49 + p^{2} = 0
Solving for variable 'p'.
Move all terms containing p to the left, all other terms to the right.
Add '49' to each side of the equation.
-49 + 49 + p^{2} = 0 + 49
Combine like terms: -49 + 49 = 0
0 + p^{2} = 0 + 49
p^{2} = 0 + 49
Combine like terms: 0 + 49 = 49
p^{2} = 49
Simplifying
p^{2} = 49
Reorder the terms:
-49 + p^{2} = 49 + -49
Combine like terms: 49 + -49 = 0
-49 + p^{2} = 0
Factor a difference between two squares.
(7 + p)(-7 + p) = 0
#### Subproblem 1

Set the factor '(7 + p)' equal to zero and attempt to solve:
Simplifying
7 + p = 0
Solving
7 + p = 0
Move all terms containing p to the left, all other terms to the right.
Add '-7' to each side of the equation.
7 + -7 + p = 0 + -7
Combine like terms: 7 + -7 = 0
0 + p = 0 + -7
p = 0 + -7
Combine like terms: 0 + -7 = -7
p = -7
Simplifying
p = -7
#### Subproblem 2

Set the factor '(-7 + p)' equal to zero and attempt to solve:
Simplifying
-7 + p = 0
Solving
-7 + p = 0
Move all terms containing p to the left, all other terms to the right.
Add '7' to each side of the equation.
-7 + 7 + p = 0 + 7
Combine like terms: -7 + 7 = 0
0 + p = 0 + 7
p = 0 + 7
Combine like terms: 0 + 7 = 7
p = 7
Simplifying
p = 7#### Solution

p = {-7, 7}